2020
DOI: 10.3390/ijms21186738
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers and Therapeutic Targets in Inflammation- and Ischemia-Reperfusion-Related Acute Renal Injury

Abstract: Acute kidney injury (AKI), caused mainly by ischemia-reperfusion, sepsis, or nephrotoxins (such as contrast medium), is identified by an abrupt decline in kidney function and is associated with high morbidity and mortality. Despite decades of efforts, the pathogenesis of AKI remains poorly understood, and effective therapies are lacking. MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression at the posttranscriptional level to control cell differentiation, development, and homeostasis. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…These novel biomarkers are related with pathological processes involved in AKI development, such as inflammation, oxidative stress and renal cells death [19,20]. Furthermore, current studies support the potential value of circulating and urinary miRNAs as novel AKI biomarkers e.g., miR-21, miR-30a-e and miR-494, among others [18,21,22].…”
Section: Biomarkers In Akisupporting
confidence: 61%
“…These novel biomarkers are related with pathological processes involved in AKI development, such as inflammation, oxidative stress and renal cells death [19,20]. Furthermore, current studies support the potential value of circulating and urinary miRNAs as novel AKI biomarkers e.g., miR-21, miR-30a-e and miR-494, among others [18,21,22].…”
Section: Biomarkers In Akisupporting
confidence: 61%
“…miRNAs have been widely reported as promising biomarkers for many diseases. In fact, they have been shown as non-invasive biomarkers in multiple diseases including cancers and renal diseases [ 14 , 15 , 16 , 17 ]. Because miRNAs may directly be associated with pathogenesis of some types of NS, to analyze miRNA profiles in NS patients is not only for the diagnosis for the specific diseases, but also for understanding and elucidating the disease pathogenesis and even for establishing novel therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemia-reperfusion injury is the main cause of acute renal injury 24 and an unavoidable problem in renal transplantation 25 . Recent studies have shown that some miRNAs are extensively involved in several organs and tissues of IRI 8 , 26 . MiR-124 has been reported to participate extensively in the pathophysiology of ischemic stroke, functioning as a protective role against cerebral ischemia-reperfusion injury 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are highly conserved small RNA molecules of 21-25 nucleotides, which have been reported to be associated with renal IRI 8 . For example, miR-687 was markedly upregulated during renal ischemia-reperfusion injury in mice and cell models 9 .…”
Section: Introductionmentioning
confidence: 99%